Studi Aliran Filsafat Pendidikan Islam Serta Implikasinya Terhadap Pengembangan Pendidikan Islam - Mughni, Muhamad Syafiq; M. Yunus Abu Bakar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The long journey of Islamic education that has grown to date is strongly influenced by the thoughts of its driving figures in implementing the existing learning system in the educational institutions they develop. The thoughts of the education driving figures are driven by the intersection between the socio-cultural realities faced by these figures with the religious thoughts they profess, namely Islam. With the literature study method, this study aims to identify the schools in Islamic educational philosophy, the purpose of this research is to find out the construction of Islamic thought, especially Muslim philosophers about education, because we know that education is a human way of life. The results of this research can later be used as a philosophical foundation for every educational practitioner. In the results of this study found the schools of Islamic education philosophy, namely 1) al-muhafid 2) Al-Diniy Al-Aqlaniy and 3) al-dzara'iy. In addition to finding the schools in Islamic educational philosophy, this study also finds the implications of these schools with the development of Islamic education curriculum. The pattern of development of Islamic education in the perspective of the al-Muhafidz school only has an orientation to form students who are aware of the hereafter, in contrast to the Al-Diniy Al-Aqlaniy school, in addition to being oriented towards the sciences of the hereafter, in its educational development this school also integrates religious education and natural education. and arithmetic. As for the flow of al-dzara'iy more to the practical sciences